Implementing Student-Centered Learning to Facilitate Students’ Reading Comprehension of Report Texts: A Case Study - Abdul Hadi; Liza Fazira (Datokarama English Education Journal, 2025)
This study sought to examine how English teachers implemented student-centered learning to facilitate students in improving their comprehension of English report texts during the process of teaching English as a foreign language to Indonesian students at a vocational high school in Riau. Employing a qualitative case study design, data for this study were gathered through classroom observations, interviews with two English teachers, and focus group discussions with two groups of students at the school. Analyses of the data showed that the implementation of student-centered learning in facilitating students’ comprehension of English report texts was communicative, as evidenced by its innovative and collaborative nature. Other findings indicated that it was both relevant to the expected learning outcomes and flexible in terms of lesson planning, classroom practice, and evaluation, as revealed through analysis of the relevant data. In general, it was concluded that the English teachers in this study were adequately successful in implementing student-centered learning to support students in developing their reading comprehension of English report texts.